Foundations of a sociology of canon law - Hahn, Judith (Springer Nature, 2022)
This "Open Access" book investigates the legal reality of the church through a sociological lens and from the perspective of canon law studies, the discipline which researches the law and the legal structure of the Catholic Church. It introduces readers from various backgrounds to the sociology of canon law, which is both a legal and a theological field of study, and is the first step towards introducing a new subdiscipline of the sociology of canon law. As a theoretical approach to mapping out this field, it asks what theology and canon law may learn from sociology; it discusses the understanding of "law" in religious contexts; studies the preconditions of legal validity and effectiveness; and based on these findings it asks in what sense it is possible to speak of canon "law". By studying a religious order as its struggles to find a balance between continuity and change, this book also contributes to the debates on religious law in modernity and the challenges it faces from secular states and plural societies. This book is of interest to researchers and students of the sociology of law, legal studies, law and religion, the sociology of religion, theology, and religious studies. This is an open access book